Identifikasi Kawasan Rawan Bencana Longsor di Desa Galala Kecamatan Mandioli Selatan Kabupaten Halmahera Selatan - Darling Surya Alnursa; Fandi Munery (Peneliti.net, 2023)
This study aims to determine the distribution of landslide-prone areas and to determine disaster mitigation in landslide-prone areas. As well as the method used in this study is a survey method with a type of qualitative research. Based on the results of the discussion on zoning with the potential for landslides, in the study area there is a potential landslide type B zone with an area of 2.24 km2 and there is a low to moderate level of landslide vulnerability. While the landslide potential zone is type C with an area of 42.46 km2 and there are high, moderate to low levels of landslide vulnerability. Land use in the type B zone is dry land agriculture and secondary dry land forest. Land use in the type C zone is settlement, dryland agriculture, shrubs, secondary dryland forest, mangroves and primary dryland forest. In addition, areas prone to landslides are at moderate to low levels. Landslides in this area have not been handled in terms of prevention, because the reason is that the landslides that occurred were far from residential areas and the level of vulnerability to landslides was low, so the area was not included in the investigation area of the Regional Disaster Management Agency (BPBD) of South Halmahera Regency.